(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
Background: Conflicts experienced by adolescents are most encountered in school environments. The most common conflict found in schools is discrimination. The phenomenon of discrimination can develop into forms of cyberbullying as commonly found on social media. To address the increasing number of bullying cases, one of the most effective ways known is by applying coping strategies. This article will discuss which coping strategies are effective in addressing the problems of discrimination and cyberbullying. Methods: This research method was carried out by identifying, analysing, reviewing, and synthesizing related research, using several keywords such as "Adolescent Coping Strategies, Discrimination, and Cyberbullying." Using PRISMA in describing Adolescent Coping Strategies in Dealing with Discrimination and Cyberbullying. Results: The coping strategies that can be used to address discrimination and cyberbullying in schools are divided into two types, namely those related to the supporting environment and psychological approaches. The supporting environment includes family and parenting styles, schools, communities, and the government. While psychological approaches include forgiveness, problem-focused coping, emotions-focused coping, emotional focus strategy, conflict stimulation methods, conflict reduction methods, conflict management methods, and other coping strategies. Conclusion: Based on the systematic literature review conducted, the dominant coping strategy used to address discrimination and cyberbullying in schools is forgiveness.